Effect of alkaline solution to fly ash ratio on geopolymer mortar properties - Fauzi, A. (Trans Tech Publications Ltd, 2017)
Geopolymer system is new binding materials in concrete industry that is produced by the alkaline solution and materials rich in aluminosilicate such as fly ash. The effect of the alkaline solution to fly ash ratios of 0.3, 0.4 and 0.5 on mortar geopolymer properties was an issue in this study. The results showed that the higher alkaline solution to fly ash ratio improves the workability and brings a longer setting time, whereas the lower alkaline solution to fly ash ratio gains the significant compressive strength. It was a similar pattern with conventional mortar used ordinary Portland cement, which the compressive strength at 7 days was 85-90 for 28 days compressive strength, whereas conventional mortar is only 65-75. This was due to the higher reactivity in geopolymer system that was faster than the pozzolanic reaction. © 2017 Trans Tech Publications, Switzerland.